Cidades, políticas culturais e participação social: uma avaliação do “Carnaval do Maranhão – Circuito Beira Mar” de São Luís-MA - LUZ, Emanuely Ferreira dos Reis (2022)
The space and the city constitute an objective reality, both social products in a permanent process of transformation. Therefore, in order to study them, it is necessary to understand the relationship they have with society, as well as the changes that this imposes on its functioning. The city, in this case, it is the inhabited and dynamic space that needs cultural public policies for its occupation and preservation. Thus, the main objective of this research is to evaluate the implementation of the strategic action "The Carnival of Maranhão in the Historic Center - Beira Mar Circuit" contained in the cultural, tourism, leisure center of the "Nosso Centro" Program. To achieve this objective, this study considered whether such action, it is formulated to contribute to the promotion of the occupation of public spaces and the realization of cultural attractions in the Historic Center of São Luís - MA. At this point, it is added that this investigation made possible new studies on the themes of city, space, democratic and citizen participation, occupation of public spaces and heritage preservation, allowing develop knowledge to the point that the results aggregate in studies on public cultural policies aimed at for public spaces, such as the Historic Centers. For this, the methodological aspects covered the documentary, bibliographic, qualitative and quantitative approach characteristics, with the application of interviews and questionnaires. Through this, the main results showed that the action of Carnival allows the occupation of society and its inhabitants in public spaces, but greater participation is necessary, since it was found that decision-making is unilateral, and with the economic objective, therefore, not cultural. In this aspect, the main understanding of this research allows to considering the strategic action of Carnival as a good practice, however, local traditions must be included, in a broader and more professional way. In addition, there is a need for an interactive participation, where there can be through dialogues, but mainly, represented by the power of decision. In this way, it was found that for social participation to occur in a democratic and citizen way, it is necessary that the public power has sensitivity, creates mechanisms and legislation that meets all types of cultural attractions, reducing bureaucracy and investing in education. Those points prioritizes citizenship, dialogue and plurality.